Airway cell composition at rest and after an all-out test in competitive rowers - Morici, G.; Bonsignore, M. R.; Zangla, D.; Riccobono, L.; Profita, M.; Bonanno, A.; Paterno, A.; Di Giorgi, R.; Mirabella, F.; Chimenti, L.; Benigno, A.; Vignola, A. M.; et al. (Medicine & Science in Sports & Exercise, 2004)
Purposes: This study was designed to assess: a) whether rowing affects airway cell composition, and b) the possible relationship between the degree of ventilation during exercise and airway cells. Subjects and Methods: In nine young, nonasthmatic competitive rowers (mean age +/- SD: 16.2 +/- 1.0 yr), induced sputum samples were obtained at rest and shortly after an all-out rowing test over 1000 m (mean duration: 200 +/- 14 s), during which ventilatory and metabolic variables were recorded breath-by-breath (Cosmed K4b, Italy). Results: At rest, induced sputum showed prevalence of neutrophils (60%) over macrophages (40%); after exercise, total cell and bronchial epithelial cell (BEC) counts tended to increase. In the last minute of exercise, mean [latin capital V with dot above]E was 158.0 +/- 41.5 L[middle dot]min-1, and [latin capital V with dot above]O2[middle dot]kg-1 62 +/- 11 mL[middle dot]min-1. Exercise [latin capital V with dot above]E correlated directly with postexercise total cell (Spearman [rho]: 0.75, P < 0.05) and macrophage ([rho]: 0.82, P < 0.05) counts. A similar trend was observed for exercise [latin capital V with dot above]E and changes in BEC counts from baseline to postexercise ([rho]: 0.64, P = 0.11). Exercise [latin capital V with dot above]E did not correlate with airway neutrophil counts at rest or after exercise. Expression of adhesion molecules by airway neutrophils, macrophages, and eosinophils decreased after the all-out test. Conclusion: Similar to endurance athletes, nonasthmatic competitive rowers showed increased neutrophils in induced sputum compared with values found in sedentary subjects. The trend toward increased BEC postexercise possibly reflected the effects of high airflows on airway epithelium. Airway macrophages postexercise were highest in rowers showing the most intense exercise hyperpnea, suggesting early involvement of these cells during exercise. However, the low expression of adhesion molecules by all airway cell types suggests that intense short-lived exercise may be associated with a blunted response of airway cells in nonasthmatic well-trained rowers.